Interligação entre Bioquímica Sanguínea e Neuromonitorização em Pacientes com Lesão Cerebral Aguda - João Pedro Cordeiro de Almeida (2020)
Acute brain injury is one of the leading causes of disability and trauma-related death amongst young individuals worldwide. Besides, it is a medical field with one of the biggest unmet needs, and its pathophysiology is not completely understood. We pursued to clarify some of the existing doubts by analysing biochemical and neuromonitoring data in patients with acute brain injury and its influence on cerebral autoregulation and patient outcome. Several studies show that methaemoglobin might have a role on the perpetuation of secondary lesion or solely as a biomarker of oxidative stress. Other biochemical parameters also seem to have an influence in cerebral autoregulation mechanisms, such as calcium. We retrospectively analysed blood gas and laboratory data from 43 patients admitted in the neurocritical care ICU from 2014 to 2016. We found that increasing values of MetHb within normal range are correlated with an increase in the pressure reactivity index (PRx), indicating disturbed pressure autoregulation, while increasing values of Ca²⁺ were associated with a decrease in PRx. Further studies are needed to evaluate possible related therapeutic targets to improve impaired autoregulation and patient outcome.